Effectiveness of Project-Based Learning in Improving Critical Thinking Skills and Environmental Concern Attitude in Vocational Students - Adawiyah, Rabiatul; Mahmuddin, Mahmuddin (Journal of Education Method and Learning Strategy, 2024)
Creating conducive learning must be supported by skills in managing classes, learning media and learning models. One learning model so that students have these skills is the project-based learning model. The aim of this research is to determine the effectiveness of implementing the project-based learning model on critical thinking skills and attitudes towards the environment. This research was conducted at vocational students in Banjarmasin City. This research uses a quantitative approach with experimental methods. The results of this research indicate that project-based learning is effective in increasing critical thinking skills and environmental concern for wetlands. This is proven by testing the effectiveness of critical thinking skills with the Asymp value. Sig. (2-tailed) is 0.003 < 0.05 and tests the effectiveness of the attitude of caring for the wetland environment with the Asymp value. Sig. (2-tailed) is 0.000 < 0.05